Оптикоелектронні методи реєстрації слабкого випромінювання - Калмиков, О. С.; Стрілкова, Т. О. (ХНУРЕ, 2019)
A review of the processes occurring in biological tissues and materials, which are accompanied by a weak glow. Methods based on the registration of chemiluminescences and fluorescence taking into account the intensity and spectrum of radiation are considered. Temporal and space-time signal filtering methods at low signal-to-noise ratios are presented. Additional statistical characteristics of the signal components are determined.
Keywords: Оптикоелектроніка; слабке випромінювання